Analysis of the strengths and weaknesses of the legal framework for compensation and payment for environmental services in Argentina - Claudia, Luna (2020)
The objective of this proposal has been to analyze the regulatory platform for compensation and payment for environmental services; the elements for an environmental services market in Argentina; to then detect the strengths and weaknesses to implement in a sustainable way, an economic and profitable recognition for the environmental services that native forests provide to society; This enables critical issues in the legal field to be identified with respect to the compensation related to their assessment as an effective tool to promote both conservation and sustainable development actions. The analysis carried out on the valuation of the ecosystem services of the native forests of Argentina; It shows that our country still has to develop a market to implement in a sustainable way, an economic and profitable recognition for the environmental services that native forests provide to society.